2017
DOI: 10.1177/1363459317745690
|View full text |Cite
|
Sign up to set email alerts
|

Smoking to fit a stigmatised identity? A qualitative study of marginalised young people in Australia

Abstract: In countries with comprehensive tobacco control, smoking is increasingly denormalised, with smokers subject to social stigmatisation. Qualitative research and commentary about denormalisation and stigma has largely focused on the impact on current or former smokers. Little attention has been given to the interaction between existing stigma among socially marginalised and disadvantaged young people and its role in smoking uptake, maintenance and resistance to quitting, or remaining a non-smoker. This article dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Thus, when smokers practice smoking at distinct places, it indicates that smoking has a negative connotation. Moreover, many smokers experienc stigmatization [ 44 , 45 ], among others, due to perceptions that smokers have a ”devalued identity” [ 7 ] (p. 313). Research has found that adolescents may feel pressured to find alternative places to smoke to demonstrate agency relative to discourses about smoking as an unhealthy behavior [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, when smokers practice smoking at distinct places, it indicates that smoking has a negative connotation. Moreover, many smokers experienc stigmatization [ 44 , 45 ], among others, due to perceptions that smokers have a ”devalued identity” [ 7 ] (p. 313). Research has found that adolescents may feel pressured to find alternative places to smoke to demonstrate agency relative to discourses about smoking as an unhealthy behavior [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with results from Moore, who found that the negative perception of smokers was ascribed to the entire identity of the person who smokes [ 47 ]. Being a smoker can result in loss of status as a consequence of smoking stigmatization [ 7 , 39 , 48 ]. The adolescents’ smoking practice and the practice of smoking at distinct places might, therefore, be a way to avoid stigmatization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A grounded theory study of 18 young (16-25 years), disadvantaged Australians described stigma internalisation, self-labelling, and experience of stereotyping. Smoking was identified as a cause and consequence of stigma and non-smoking was linked to stigma resistance [68]. Stigma resistance against being viewed as an "irresponsible smoking mother" has been reported in Scottish disadvantaged mothers [36], (p.499).…”
Section: Discussionmentioning
confidence: 99%